The solution to the equation 3(2 + 3 + 5), 13(9 + 6 - 3), (9 + 6 - 3) ÷ 3, 3(2. 3. 5) and 3 ÷ (9 + 6 - 3) is 30, 156, 4, 90 and 1/4 respectively
An equation is an expression that shows the relationship between two or more numbers and variables.
a) 3(2 + 3 + 5)
= 3(10) = 30
b) 13(9 + 6 - 3)
= 13(12) = 156
c) (9 + 6 - 3) ÷ 3
= 12 ÷ 3 = 4
d) 3(2. 3. 5)
= 3(30) = 90
e) 3 ÷ (9 + 6 - 3) = 3 ÷ 12 = 1/4
The solution to the equation 3(2 + 3 + 5), 13(9 + 6 - 3), (9 + 6 - 3) ÷ 3, 3(2. 3. 5) and 3 ÷ (9 + 6 - 3) is 30, 156, 4, 90 and 1/4 respectively
Find out more on equation at: https://brainly.com/question/2972832
#SPJ1